MINAT GENERASI Z DALAM BERWAKAF UANG MELALUI PEMANFAATAN TEKNOLOGI DIGITAL PADA PLATFORM KEUANGAN - Dini zahratun husna; Faris Affandi; Muhammad Arfan Harahap (INTERNATIONAL, Journal of Sharia Business Management, 2025)
Cash waqf is an Islamic philanthropic instrument with significant potential to support economic and social development. However, the level of participation of Generation Z in cash waqf remains relatively low despite their large population and digital-native characteristics. This study aims to analyze the factors influencing Generation Z’s interest in cash waqf. The research employs a quantitative approach using questionnaire-based data collected from Generation Z respondents. The variables examined include cash waqf literacy, religiosity, trust in waqf management institutions, utilization of digital technology, and ease of access to information. The data were analyzed using multiple linear regression to determine the effect of each variable on interest in cash waqf. The findings indicate that cash waqf literacy, institutional trust, and the use of digital technology have a significant positive effect on Generation Z’s interest in participating in cash waqf. Meanwhile, religiosity and access to information show a weaker influence. This study is expected to serve as a reference for waqf institutions in developing strategies to enhance cash waqf participation by aligning programs with the characteristics and preferences of Generation Z.